Antibiotic use for respiratory infections among Hajj pilgrims: A cohort survey and review of the literature. Issue 30 (July 2019) - Hoang, Van-Thuan; Nguyen, Thi-Thu-Thuy; Belhouchat, Khadidja; Meftah, Mohammed; Sow, Doudou; Benkouiten, Samir; Dao, Thi-Loi; Anh Ly, Tran Duc; Drali, Tassadit; Yezli, Saber; Alotaibi, Badriah; Raoult, Didier; et al.
Abstract: Background: To evaluate the occurrence and determinants associated with antibiotic use for respiratory tract infections (RTIs) among Hajj pilgrims. Methods: Prospective cohort surveys were conducted among French pilgrims from 2012 to 2017. We also conducted a systematic review about available evidence for antibiotic consumption in relation with RTIs during the Hajj. Results: 783 pilgrims were included in the survey. During the Hajj, 85.3% presented respiratory symptoms and 47.6% used antibiotics. Pilgrims with productive cough or fever were three times and twice as likely to have used antibiotics. Dry cough, sore throat and voice failure were also associated with increased antibiotic use. 26.3% of pilgrims presented symptoms compatible with a lower tract respiratory infection. According to the French recommendations, only 39.6% of pilgrims who used an antibiotic actually had an indication for it. Antibiotic intake was associated with an increased frequency of persistent symptoms post-Hajj (aRR = 1.31, 95%CI [1.04–1.66]). The review included 14 articles. The use of antibiotic for respiratory tract infections during the Hajj varied from 7% to 58.5%. In 9 studies, the antibiotic consumption rate was >30%. Conclusion: Respiratory tract infections are common during the Hajj, leading to high prevalence of inappropriate antibiotic intake.